2010
DOI: 10.1103/physrevlett.105.163001
|View full text |Cite|
|
Sign up to set email alerts
|

Nonsequential Two-Photon Double Ionization of Atoms: Identifying the Mechanism

Abstract: We develop an approximate model for the process of direct (nonsequential) two-photon double ionization of atoms. Employing the model, we calculate (generalized) total cross sections as well as energy-resolved differential cross sections of helium for photon energies ranging from 39 to 54 eV. A comparison with results of ab initio calculations reveals that the agreement is at a quantitative level. We thus demonstrate that this complex ionization process is fully described by the simple model, providing insight … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
(62 reference statements)
4
15
0
Order By: Relevance
“…The model leads to a simple expression of the differential TPDI cross section (since the TPDI probability varies linearly with T within LOPT it is appropriate to calculate cross sections); see Eq. (8) in [3]. The results agree qualitatively and quantitatively with other calculations, at least for ω > 1.84 (50 eV), where it is not critical for the electrons to interact strongly in order to overcome the attraction of the nucleus [2].…”
Section: The Direct Regime (ω < 2)supporting
confidence: 88%
See 1 more Smart Citation
“…The model leads to a simple expression of the differential TPDI cross section (since the TPDI probability varies linearly with T within LOPT it is appropriate to calculate cross sections); see Eq. (8) in [3]. The results agree qualitatively and quantitatively with other calculations, at least for ω > 1.84 (50 eV), where it is not critical for the electrons to interact strongly in order to overcome the attraction of the nucleus [2].…”
Section: The Direct Regime (ω < 2)supporting
confidence: 88%
“…In addition to these discrepancies between theoretical results, there is a new issue, namely, the sharp rise of the TPDI cross section around 2 a.u. [3][4][5][6][7][8], that is the subject of ongoing debates [9]. This brings our attention to TPDI in the threshold region of the sequential process, i.e., at photon energies close to 2 a.u.…”
Section: Introductionmentioning
confidence: 99%
“…3. Recently, it was predicted that the anti-U shape could also appear in neon at lower photon energies [32], and it has furthermore been suggested that the energy spectrum of helium has a negative concavity near the line in the figure shows the corresponding SDCS obtained for helium at the photon energy 40 eV, close to the lower threshold in helium (39.4 eV), and indeed a slightly negative concavity is observed. The SDCS result for helium (40 eV) was derived from a pulse 7 fs in duration and extracted by projecting onto Z = 2 Coulomb waves.…”
mentioning
confidence: 66%
“…As a rather complete understanding of the process of one-photon double ionization of helium is emerging [17,18] the related process of nonsequential two-photon double ionization (TPDI) is currently receiving considerable theoretical [12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and experimental [36][37][38][39][40][41] attention. Recently, TPDI of H 2 by 30-eV photons was studied theoretically [42][43][44], and clear discrepancies in the calculated tripledifferential cross sections were identified.…”
mentioning
confidence: 99%
“…The one-photon and two-photon double ionization of helium has attracted remarkable attention [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] since these processes provide a wonderful chance to investigate the fundamental two-electron correlation, which is related to the long-standing three-body Coulomb problem. Direct coincidence measurements on the fully differential two-electron momentum distributions can provide detailed information about the process of double ionization.…”
Section: Introductionmentioning
confidence: 99%